Factors affecting performance response of pigs exposed to different challenge models: a multivariate approach. (1st June 2021) - Rodrigues, Lucas A; Ferreira, Felipe N A; Costa, Matheus O; Wellington, Michael O; Columbus, Daniel A
Abstract: Factors associated with the severity with which different challenge models (CM s) compromise growth performance in pigs were investigated using hierarchical clustering on principal components (HCPC ) analysis. One hundred seventy-eight studies reporting growth performance variables (average daily gain [ADG ], average daily feed intake [ADFI ], gain:feed [GF ], and final body weight [FBW ]) of a Control (Ct ) vs. a Challenged (Ch ) group of pigs using different CMs (enteric [ENT ], environmental [ENV ], lipopolysaccharide [LPS ], respiratory [RES ], or sanitary condition [SAN ] challenges) were included. Studies were grouped by similarity in performance in three clusters (C1, C2, and C3 ) by HCPC. The effects of CM, cluster, and sex (males [M ], females [F ], mixed [Mi ]) were investigated. Linear (LRP ) and quadratic (QRP ) response plateau models were fitted to assess the interrelationships between the change in ADG (∆ADG ) and ADFI (∆ADFI ) and the duration of challenge. All variables increased from C1 through C3, except for GF, which decreased ( P < 0.05). LPS was more detrimental to ADG than ENV, RES, and SAN models (P < 0.05). Furthermore, LPS also lowered GF more than all the other CMs ( P < 0.05). The ∆ADG independent of ∆ADFI was significant in LPS and SAN ( P < 0.05), showed a trend toward the significance in ENT and RES ( P < 0.10), and was not significant in ENV ( P > 0.10), while the ∆ADG dependent on ∆ADFI was significant in ENT, ENV, and LPS only ( P < 0.05). The critical value of ∆ADFI influencing the ∆ADG was significant in pigs belonging to C1 ( P < 0.05) but not C2 or C3 ( P > 0.10). The ∆ADG independent of duration post-Ch (irreparable portion of growth) was significant in C1 and C2 pigs, whereas the ∆ADFI independent of duration post-Ch (irreparable portion of feed intake) was significant in C1 pigs only ( P < 0.05). Moreover, the time for recovery of ADG and ADFI after Ch was significant in pigs belonging to C1 and C2 ( P < 0.05). Control F showed reduced ADG compared with Ct-M, and Ch-F showed reduced ADFI compared with Ch-M ( P < 0.05). Moreover, the irreparable portion of ΔADG was 4.8 higher in F (−187.7; P < 0.05) compared with M (−39.1; P < 0.05). There are significant differences in growth performance response to CM based on cluster and sex. Furthermore, bacterial lipopolysaccharide appears to be an appropriate noninfectious model for immune stimulation and growth impairment in pigs.